(untitled) (Research, Society and Development, 2020)
The environmental impacts caused by man and the advancement of the concept of environmental sustainability made it necessary to classify and quantify the performance of governments and the population with regard to sustainability. The so-called ‘sustainability indicators’ serve to analyze the degree of environmental impacts caused in different media. The ecological footprint is one of the main known sustainability indicators, as it assesses the natural resources, the consumption pattern of the populations and verifies whether these patterns are within the country’s ecological capacity. The objective was to calculate the ecological footprint in two schools in the municipality of Pombal, in the state of Paraíba, one public and one private school. The ecological footprint was calculated by applying a multiple-choice questionnaire relating different themes. The Ecological Footprint of private school students was higher than that of public schools, but both exceeded the world average. It was possible to observe that the students’ income is positively related to the environmental impacts caused by them. Promoting greater awareness of students from both schools is essential to reduce environmental impacts.